A dynamic panel data: causality test on export led growth hypothesis / Kamarudin Othman, Fathiyah Ismail and Roseziahazni Abd Ghani - Othman, Kamarudin; Ismail, Fathiyah; Abd Ghani, Roseziahazni (2011)
This paper used a panel data approach to investigate the export led growth hypothesis (ELGH) for 10 selected OIC countries from 1978 to 2000. The 10 OIC countries were clustered into Asian, African and Middle Eastern groups. The GMM-SYS was employed to estimate the VAR panel data model for 10 OIC countries as a whole and each sub-group. From the empirical analysis we discovered that, for the 10 OIC countries as a whole the result showed that export and growth had uni-directional relationship and it supported the export led growth hypothesis (ELGH). But after we clustered the 10 OIC countries into three groups, the result was contradictory. The results from Asian group did not support the export led growth hypothesis. Meanwhile, bi-directional positive casual relationship presented in the African group. For the Middle East group, the empirical evidence showed that export and growth have a positive causal relationship.